Subordinate responses to leadership: evidence from an emerging market firm - Arbaiza, Lydia (2016)
This paper was conducted to examine the effect of paternalistic and Western leadership style using a sample of 326 subordinates. Due to insufficient number of studies about the type of relationship between subordinates’ responses and leadership type, this study aimed to determine whether paternalistic and Western leadership has a positive impact on managing subordinates. The respondents are employed at a wide variety of firms around Peru, such as Banking, Informational Technology, Commerce, Supply Chain, Construction and Law. A quantile regression was conducted to determine the effects of different types of paternalistic leadership such as benevolent leadership, moral leadership, and authoritarian on subordinate responses. The findings revealed that paternalistic leadership had a positive influence on compliance and gratitude while transformational leadership had a positive influence on gratitude. The survey was limited to Lima due to the current researcher did not have access to subordinate interviews throughout the Latin American Region. The results of this study were relevant to leadership theory and practices that can be implemented in Peruvian firms.